What types of nature exposure are associated with hedonic, eudaimonic and evaluative wellbeing? : An 18-country study - McDougall, Craig W.; Elliott, Lewis R.; White, Mathew P.; Grellier, James; Bell, Simon; Bratman, Gregory N.; Nieuwenhuijsen, Mark; Lima, Maria L.; Ojala, Ann; Cirach, Marta; Roiko, Anne; van den Bosch, Matilda; et al. (Academic Press, 2024)
Although spending time in nature can improve subjective wellbeing (SWB), little is known about how different types of nature exposure are associated with different dimensions of SWB or the consistency of associations across national/cultural contexts. Using data from 18 countries, associations between green, coastal and freshwater blue space exposures (including residential availability, visits ‘yesterday’ and visits in the previous four weeks) and hedonic, eudaimonic, and evaluative wellbeing were estimated. Overall, residential nature availability showed little association with any wellbeing outcome, whereas visiting green and coastal locations ‘yesterday’ was associated with better hedonic wellbeing. Although frequently visiting green, coastal and freshwater spaces were all associated with greater evaluative wellbeing, greater eudaimonic wellbeing was only associated with frequent visits to green and freshwater spaces. Variations existed across countries. Results suggest that different types of nature exposure vary in their association with different dimensions of SWB. Understanding these differences may help us maximise the potential of natural environments as SWB-promoting resources.
Keywords: nature; blue space; happiness; public health; life satisfaction